Polyhydroxyalkanoate Producing Potential of Saccharomyces cerevisiae - S. O. Jimoh; F. O. Akinwande; O. A. Ayinde; T. Y. Senbadejo (Fountain Journal of Natural and Applied Sciences (FUJNAS), 2018)
Polyhydroxyalkanoates (PHAs) are inclusion bodies accumulated by some microorganisms as reserve material under unbalanced growth condition such as limited oxygen, nitrogen, phosphorous or sulphur and excess carbon source. Saccharomyces cerevisiae strains were screened for Polyhydroxyalkanoates (PHA) producing potential using plate assay technique with Sudan Black B stain.  Saccharomyces cerevisiae efficiency for PHA production was analysed utilizing sawdust as carbon source and the production rate was compared with glucose (control). Thus, PHA synthesising enzymes, PHA carbon chain distributions and concentrations were determined using gas chromatography flame ionization detector (GCFID) while microbial growth (biomass yield) during production was determined using Uv-Visible spectrophotometric technique at 600 nm. PHA was extracted from Saccharomyces cerevisiae cells using solvent extraction technique and the extract was further dissolved using acetone derivatisation process. PHA-synthesising enzymes such as Glyceraldehyde-3-phosphate dehydrogenase, Pyruvate dehydrogenase,  3-Ketothiolase, Acetoacetyl-CoA reductase,  3-Ketoacyl reductase and Polyhydroxyalkanoate synthase were extracted from cell-free supernatant obtained from glucose and sawdust media. Saccharomyces cerevisiae cells grown in sawdust medium had the highest PHA yield of 75.12 % while 64.66 % PHA was obtained from cells grown in glucose medium. Consequently, utilization of Saccharomyces cerevisiae in limiting condition using agricultural residue could reduce the cost of industrial production of PHA required for plastic production due to its ability to accumulate the polymer intracellularly.